The influence of some managemental programmes on maternal anomalies and pup's performance in White New Zealand rabbits - Emeash H.H.; Karousa M.M. (Rabbit production in hot climates, 1994)
Twelve New Zealand White adult female rabbits and three fertile bucks were used. The normal and abnormal maternal behaviour and pup's performance were observed and recorded. The influences of some managemental programmes on maternal anomalies and pup's performance were also studied. The results revealed that the abnormal maternal behaviour was recorded in six females which were housed in the lower row of rabbit cages. After application of some managemental changes, the abnormal maternal behaviours showed a significant decline. The percent of abnormal does which cannibalized their youngs reduced from 66.9 to 30.0 per cent and the scattering young from 50.0 to 16.0 per cent in comparison with those does that were in correct managemental environment. The survival percent of pups through weaning for normal does (78.0 percent) was significantly higher (P less than 0.05) than that of the abnormal ones (12.8 percent), the last percent would be corrected to 56.8 percent after application of some managemental programmes. The average body weight of pups from birth to weaning in the normal does was significantly higher (P less than 0.05) than that of the abnormal does. On the other hand there was no significant difference in the average litter size between the normal and abnormal does before and after managemental changes.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)